2D simulation of assistive grouser mechanism using discrete element method (dem) for traversing on unconsolidated soft sand - Siti Suhaila, Sabarudin (2022)
Wheeled rovers are one type of mobile robot used to drive over rough terrain, with an advantage for being energy efficient on a flat surface with reasonable traction force. One of the challenges of wheeled rovers in actual operation is the tendency for the wheel to sink into the sand surface when traversing on an unconsolidated sand surface incline. Many previous studies have been done to improve rover mobility performance. One of the studies proposed an “assistive grouser” attached to the side of the wheel to minimize the sinkage problem when traversing on a steep slope of soft sand. However, during the experimental test alone, the interaction between the grouser-sand cannot be seen clearly. Therefore, in this study, a simulation modelling was carried out to observe the effect of assistive grousers on sand-grouser interaction. This simulation was divided into three phases, Phase 1 simulates multiple fixed and assistive grousers attached to a wheel (Conventional Wheel - CW 80 mm and Assistive Wheel - AW 90 mm), Phase 2 simulates a single fixed and assistive grouser attached to a wheel (CW 20 and 80 mm, AW 50 and 90 mm), and Phase 3 simulates a single assistive grouser with different sinkage length (10, 20, 30 and 40 mm) and grouser angle of attack (0 and 30-degree). The observation focuses on the flow of sand particles during grouser movement, whether the grouser transfers its energy to push the wheel forward or waste energy excavating sand from below the surface (digging). From Phase 1, it can be concluded that CW 80 mm and AW 90 mm will generate a significant amount of traction force for the wheel to move forward from high values of average particle displacement value (CW 80 mm has higher -6 mm), high values of average particle velocity magnitude (CW 80 mm has higher -0.414 m/s) and high values of total displaced particle (AW 90 mm has higher 9790 particles). However, usage of CW 80 mm has also shown an increased tendency for the wheel to enter the stuck stage as the grouser lifts more sand from under the surface upward but not when using AW 90 mm. From Phase 2, the results show that for both 0 and 30-degree inclination slope, longer grouser (CW 80 and AW 90 mm) has better performance in generating forward traction force than shorter grouser (CW 20 mm and AW 50 mm). However, when using CW 80 mm, the value of negative pushing force (upward push) is higher (-100 N on 0-degree slope and -190 N on 30-degree slope). This condition indicates that the grouser experiences resistance when moving from under the wheel toward the surface. However, by using AW 90 mm, there is minimal negative force value because of the translational movement of the assistive grouser. So, there is less tendency for the grouser to dig the sand surface. From Phase 3, it was concluded that longer grouser sinkage length (40 mm) gives better performance compared to shorter sinkage length because of high average particle displacement (-55 mm for X-axis, 54 mm for Y-axis), high grouser pushing force (688 N) and larger destructive area (1803.53 mm2). The performance of the assistive grouser was reduced when climbing the inclination slope. When climbing the 30-degree slope, the average particle displacement and the grouser pushing force is smaller. But this has been solved by setting the grouser angle of attack to be the same as the slope inclination angle. On a 30-degree slope, the grouser angle of attack 30-degree is more suitable to be used because it can generate higher grouser pushing force and a higher average particle displacement. In conclusion, the simulation carried out by this study has successfully verified the assumptions and justifications related to the flow of sand particles and grouser performance that was applied during previous work to explain the better performance of assistive grousers on a steep slope of soft sand inclines.